Block Chain Technology and Human Resource Accounting – an Insight - R.Alamelu, R.Amudha, S.Dinesh, R.Nalini, A.K.Parthasaarathy (International Journal of Advanced Science and Technology, 2020)
Block chain is an accounting technology and bookkeeping innovation. It is all about the exchange of responsibility for, and keeping up a record of precise budgetary data. By and by, exchanges between organizations prompt a kind of 'fourfold section accounting', where each organization does their own particular twofold passage, and in principle the two arrangements of passages are equivalent in esteem. This model could be generously modified by block chain. In the modern business world, the key to success and sustainability is to ensure that right person is appointed for the right job, in this connection, best man-power inventory should be framed, and this is possible only through proper and effective adaptation of Human Resource Accounting. This could be possible by acclimatizing with Block chain technology. It isn't a solitary innovation, but instead a convention – a method for doing things – for recording exchanges. In this research paper, the authors have made an attempt to analyze the impact of block chain technology in the context of Human Resource Accounting (HRA) disclosure practices adopted by the various Indian corporate sectors including IT.Keywords: Block chain Technology; Human Resource Accounting; Accounting technology; Value of Human Resources